The Influence Of Servant Leadership On Work Engagement : Role Of Meaningfulness Of Work, Job Crafting, And Person-Job Fit As Mediators In NPO - Safira Nurmalitasaria; Elok Savitri Puspitarini (UNIVED Press, 2024)
Improving work engagement holds paramount importance for organizations striving to meet objectives, particularly in Indonesia where enhancing employee efficiency is a primary concern. Rooted in the Conservation of Resources and Social Exchange Theory, proactive engagement significantly enhances organizational productivity. This research aims to explore whether the meaningfulness of work, job crafting, and person-job fit, acting as mediators, can intervene in the relationship between servant leadership as independent variables, and work engagement as the dependent variable. Empirical data are being collected through the distribution of questionnaires to 250 members in one of NPO in Semarang. Structural Equation Modeling via SMART PLS 3.0 is facilitating data analysis and hypothesis testing. The findings show that servant leadership and job crafting significantly enhance the meaningfulness of work and work engagement. Positive correlations exist between servant leadership, job crafting, person-job fit, and work engagement. The study underscores the meaningfulness of work, job crafting, and person-job fit as crucial influencers of work engagement, acting as mediators in the relationship between servant leadership and work engagement. The outcomes of this research offer practical insights for academics and professionals in human resource management and non-profit organizational development in Indonesia. They underscore the importance of reinforcing determinants or antecedents of servant leadership within organizational frameworks to bolster work engagement and fulfill organizational responsibilities